2016
DOI: 10.1021/acsami.6b00391
|View full text |Cite
|
Sign up to set email alerts
|

Sputtering Deposition of Sandwich-Structured V2O5/Metal (V, W)/V2O5 Multilayers for the Preparation of High-Performance Thermally Sensitive VO2 Thin Films with Selectivity of VO2 (B) and VO2 (M) Polymorph

Abstract: For specific application to an uncooled infrared detector, VO2 thin films should have a series of characteristics including purposefully chosen polymorphs, accurate stoichiometry, phase stabilization, a high temperature-coefficient of resistance (TCR), and suitable square-resistance. This work reports controllable preparation of high-performance VO2 films via post annealing of a sandwich-structured V2O5/metal (V, W)/V2O5 multilayer precursor, which was deposited by RF magnetron sputtering. This sandwich struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 30 publications
1
37
0
Order By: Relevance
“…The metastable VO 2 (B) thin films can be prepared by popular film deposition techniques, including pulsed laser deposition [1,[14][15][16][17], metal-organic chemical vapor deposition [13,18], ion beam sputtering [3], and magnetron sputtering [9,[19][20][21][22]. In general, all these deposition processes could be summarized into two routes: the one-step route by direct deposition at high temperature, and the two-step route by deposition first at low temperature and a follow-up heat treatment at high temperature.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The metastable VO 2 (B) thin films can be prepared by popular film deposition techniques, including pulsed laser deposition [1,[14][15][16][17], metal-organic chemical vapor deposition [13,18], ion beam sputtering [3], and magnetron sputtering [9,[19][20][21][22]. In general, all these deposition processes could be summarized into two routes: the one-step route by direct deposition at high temperature, and the two-step route by deposition first at low temperature and a follow-up heat treatment at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that doping W 6+ ions increases the number of 3d state electrons and thus decreases the thermal activation energy, hence to enhance TCR value and reduce resistivity concurrently [9,21,24]. Doping has also an effect on VO 2 (B) crystallization behavior [1,9,14,21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…VO 2 smart coatings are usually used in two forms including flexible foils based on VO 2 nanoparticles [31,[43][44][45][46][47][48][49] and VO 2 based multilayer films [11,12,30,[50][51][52]. However, for commercial application as smart coatings on energy efficient fenestrations, there are still several obstacles severely limiting the relative applicability of VO 2 smart coatings.…”
Section: Introductionmentioning
confidence: 99%